A biomechanical analysis of spike motion for different skill levels of male volleyball players - Marquez, W. Q.; Masamura, M.; Ae, M. (ISB Congress, 2005)
The purpose of this study was to three-dimensionally analyze the spike motion for world elite and Japanese university volleyball players, and identify differences in swing motion to obtain information for coaching spike techniques.